Naive and regulatory B-cell transcription patterns guide the increased risk of papillary thyroid carcinoma in obesity: Obesity's influence on papillary thyroid cancer - Yu, Zihui; Xu, Ziying; Li, Shang; Tian, Ziyan; Yuan, Jing (Cellular and Molecular Biology, 2024)
A growing number of studies suggest a positive association between obesity and the high incidence of papillary thyroid cancer (PTC), suggesting that the abnormal levels of adipokines associated with obesity may be a risk factor for these aggressive thyroid cancers, but the underlying regulatory mechanisms are not yet clear. We downloaded bulk RNA sequence data for subcutaneous adipose tissue (SAT) in obesity and healthy population and tumor tissues of PTC from GEO database. Through analysis of Differential Expression Genes (DEGs), Gene Set Variation Analysis (GSVA) and Weighted Correlation Network Analysis (WGCNA), we identified co-expressed genes between obesity and PTC, and their pathways were mainly enriched in the regulation of B-cells. Furthermore, through TCGA-THCA (thyroid carcinoma) cohorts analysis, we identified B-cell regulatory-related genes LEF1, TNFRSF13C, SHLD2 and SHLD3 as independent prognostic markers of PTC. Next, we explored the transcriptional regulation mechanism of the increased risk of PTC in obesity through analysis of DNA methylation CpGs data and single-cell RNA sequences (scRNA-seq) from GEO database. PTC-induced hypomethylation of the promoter region may be involved in the transcriptional regulation of these genes, while these genes were further identified in naive and regulatory B-cells of both diseases. Notably, both of the gene expressions in naive and regulatory B-cells showed high similarity in both diseases. Our data reveals the high frequency of PTC in obese populations may be explained by the comparable transcriptional patterns of naive and regulatory B-cells, and offers novel insights for the analysis of critical genes and underlying biological mechanisms for obesity and PTC.